Exercising educational equity using California’s physical fitness data: a call for more school physical fitness programs, data, and research - Templeton, Da’Shay; Korchagin, Ruslan (Frontiers in Education, 2024)
Childhood obesity has risen and is one of the most important global problems of our time, and school physical education programs are the key to ameliorating it. In American schools, physical fitness scores have declined; yet, global, national, state, and local concerns for the overall health, physical fitness, and wellbeing of children are at an all-time high. The lack of safe and affordable options for physical activity coupled with the significant decrease in physical activity rates among most American children underscores the need for programs, data, and research on physical fitness in schools, where children spend a significant amount of their time. The purpose of this brief research report is to call the federal government and states to mandate physical fitness programs and to increase data collection capacity on physical fitness in schools. Subsequently, this study asks researchers to study physical fitness in schools in the U.S. to increase its importance to policy makers and educational stakeholders and advance our understanding of educational inequities in school physical fitness. As an example, using descriptive analyses, we have provided policymakers, educational stakeholders, and researchers with a first look at California’s physical fitness data which shows how our findings complement prior literature as well as extend them. Implications for the research and practice are discussed.